Spin-defect qubits in two-dimensional transition metal dichalcogenides operating at telecom wavelengths - Lee, Yeonghun; Hu, Yaoqiao; Lang, Xiuyao; Kim, Dongwook; Li, Kejun; Ping, Yuan; Fu, Kai-Mei C.; Cho, Kyeongjae (Nature communications, 2022)
Solid state quantum defects are promising candidates for scalable quantum information systems which can be seamlessly integrated with the conventional semiconductor electronic devices within the 3D monolithically integrated hybrid classical-quantum devices. Diamond nitrogen-vacancy (NV) center defects are the representative examples, but the controlled positioning of an NV center within bulk diamond is an outstanding challenge. Furthermore, quantum defect properties may not be easily tuned for bulk crystalline quantum defects. In comparison, 2D semiconductors, such as transition metal dichalcogenides (TMDs), are promising solid platform to host a quantum defect with tunable properties and a possibility of position control. Here, we computationally discover a promising defect family for spin qubit realization in 2D TMDs. The defects consist of transition metal atoms substituted at chalcogen sites with desirable spin-triplet ground state, zero-field splitting in the tens of GHz, and strong zero-phonon coupling to optical transitions in the highly desirable telecom band. Defect centers in two-dimensional materials has shown promise for applications in quantum information and sensing. Lee et al. computationally discover a class of substitutional defect centers in monolayer transition metal dichalcogenides with promising qubit characteristics operating at telecom wavelengths.